Two Armenian Personal Names With Šah ‘King’ - Martirosyan, Hrach («Վառմ» տպ.)
There are a great number of Armenian compound personal names with the element šah ‘king’ of Iranian origin (Middle Persian and New Persian šāh ‘king’). It occurs: in both masculine and feminine names; with both native Armenian and foreign components; either as the first or the second component; often in doublet forms with a reversed order of the components. For instance: masculine Šah-amir and Amir-šah, Šah-paron and Paron-šah, Vahram-šah; feminine: Šah-xat‘un and Xat‘unšah, Šah-tikin. Also note masc. Šah-aziz vs. fem. Aziz-šah, masc․ Sult‘an-šah vs. fem. Šah-sult‘an, masc. Melik‘-šah vs. fem. Šah-melē/ik‘2 (the latter is sometimes masculine, cf. Middle Persian > Syriac Šāh-malīk, also masculine3). This paper aims to interpret two hapax legomena in which the component šah became synchronically unanalyzable due to phonological changes. In one of them, šah is the second member of the name (gen. Artamšin < *Artam-šah/y-in), whereas in the other it is the first one (Šaštʻi < *Šah-stʻi ‘Šah-Lady’).
Keywords: Personal names